Do fato contábil ao fato jurídico tributário: pressupostos para a incidência do imposto sobre a renda na redução de passivos - Holanda, Rodrigo Schwartz (2020)
This study aims to evaluate the necessary assumptions so that the net worth increase experienced by the extinction of obligations under more advantageous conditions than those initially agreed is consistent with the taxation of income tax. Legal relations are dynamic. Rights and duties are formed and, not infrequently, are extinguished in terms and conditions that differ from those initially foreseen or agreed, sometimes more advantageous for one of the parties. When this occurs, it is possible that one part of the legal relationship will gain. Such a gain, however, may not always be subject to Income Tax. To identify the conditions and assumptions necessary for the tax to be levied, an analysis of the approximations and distances related to how the financial statement, the starting point for the identification of the tax calculation base, was carried out, highlights this phenomenon. The controversial point, as a rule, stems from the fact that tax legislation lends to accounting science the function of making the linguistic report that identifies the asset increase capable of being subject to the tax, which imposes that the interpreter of the Law cannot handle the accounting result uncritically. The matter is cause for tension between taxpayers and the Federal Finance Administration and moves the Brazilian courts. The objective is to contribute to the interrelationship between Law and Accounting and the understanding of this phenomenon